2015
DOI: 10.1108/ijppm-06-2013-0109
|View full text |Cite
|
Sign up to set email alerts
|

Key observations from a survey about Six Sigma implementation in Brazil

Abstract: Purpose – The purpose of this paper is to present a survey on Six Sigma and key observations on which variables/management practices are the most important for a successful Six Sigma implementation, as well as the strengths and weaknesses of the practices observed in companies in Brazil. Design/methodology/approach – Five research questions were proposed, and an exploratory field study was carried out. A sample of 103 questionnaires was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Questionnaire Jesus et al (2015) Entrepreneurs seek on their own the implementation of quality programs and senior management is compromised. However, there are external reasons such as environmental and consumer protection laws that require managers to pursue quality programs, and often they are unaware of how to implement it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire Jesus et al (2015) Entrepreneurs seek on their own the implementation of quality programs and senior management is compromised. However, there are external reasons such as environmental and consumer protection laws that require managers to pursue quality programs, and often they are unaware of how to implement it.…”
Section: Methodsmentioning
confidence: 99%
“…organizations underwent a restructuring in an attempt at more agile internal communication (Berssaneti et al, 2016). Two studies have shown that management recognizes the performance of multiple tasks by employees, as something representative for organizations; however, do not apply Job Rotation, a process that establishes a rotation of functions (Jesus et al, 2015;Jacques et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In statistical terms, Six Sigma means 3.4 defects per million opportunities (DPMO). Sigma (σ) is the term used to represent the variation about the mean of a process (Jesus, Antony, Lepikson, & Cavalcante, 2015). In terms of business, Six Sigma is a strategy used to improve business profitability by eliminating waste, reducing the costs associated with poor manufacturing quality and improving the effectiveness and efficiency of all operations to meet or exceed the needs and expectations of customers (Coronado & Antony, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although TQM triggered the human community to apply numerous tools and techniques to achieve continuous quality improvement, their impact on achieving business results was not very impressive [20]. In order to tune the TQM to meet the needs of achieving business results, Six Sigma was developed by Bill Smith in Motorola in the year 1987 [14]. As mentioned in the previous section, the companies which implemented Six Sigma gained significant financial benefit [21].…”
Section: History and Growth Of Six Sigmamentioning
confidence: 99%
“…This development was even termed by some authors as 'Big Dollar Impact'. The objective of Six Sigma is to ensure that the companies implementing it should produce less than 3.4 defects per million opportunities (DPMO) [3,13,14]. This value is very nearer to zero-defect manufacturing level.…”
Section: Introductionmentioning
confidence: 99%